2008
DOI: 10.1136/hrt.2008.142836
|View full text |Cite
|
Sign up to set email alerts
|

Early increase of carotid intima-media thickness in children with parental history of premature myocardial infarction

Abstract: Background/objective: Increased carotid intima-media thickness (IMT) is an early manifestation of atherosclerosis. Our group has previously demonstrated that a parental history of premature myocardial infarction (PHPMI) is associated with an increase in carotid IMT in children-adolescents (mean age 13 years) and young adults (mean age 24 years). The aim of the present study was to evaluate if carotid structural changes are detectable in young children with PHPMI. Methods: 26 healthy children (9 males and 17 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
2
20
0
2
Order By: Relevance
“…We found preterm offspring of hypertensive pregnancies had, on average, a 0.15-mm greater carotid wall thickness compared with term controls. The levels of thickness in our term controls were equivalent to those previously reported in healthy young adults, 29 and the differences may in part be determined by the prematurity and higher levels of cardiovascular risk factors, such as blood pressure and lipids, which are well known to relate to carotid intima-media thickness in young adult life. However, there was also an Ϸ0.05-mm difference between normotensive and hypertensive preterm offspring in whom levels of risk factors were equivalent.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We found preterm offspring of hypertensive pregnancies had, on average, a 0.15-mm greater carotid wall thickness compared with term controls. The levels of thickness in our term controls were equivalent to those previously reported in healthy young adults, 29 and the differences may in part be determined by the prematurity and higher levels of cardiovascular risk factors, such as blood pressure and lipids, which are well known to relate to carotid intima-media thickness in young adult life. However, there was also an Ϸ0.05-mm difference between normotensive and hypertensive preterm offspring in whom levels of risk factors were equivalent.…”
Section: Discussionsupporting
confidence: 63%
“…However, there was also an Ϸ0.05-mm difference between normotensive and hypertensive preterm offspring in whom levels of risk factors were equivalent. This observation is novel, and the increase in carotid wall thickness is equivalent to that reported in young adults with a family history of cardiovascular disease 29,30 and 4 times that observed in young adult smokers. 49 The difference may be accounted for by the independent association between endothelial dysfunction and progression of carotid wall thickness.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies comparing carotid intima-media thickness and aortic stiffness in normotensive children of hypertensive parents with children of normotensive parents revealed that carotid intimamedia thickness increased in both adolescents and young adults. [24][25][26][27][28][29][30][41][42][43][44] Evelein et al 27 found that carotid intima-media thickness was higher in children older than 5 years of age compared to controls, an increase that may be observed as early as at the age of 5. Xiang et al 26 evaluated 206 children aged 16 years and older from 69 hypertensive families and demonstrated that carotid intima-media thickness was increased, an increase that correlated with both age and Arterial features in children of hypertensive parents A Yildirim et al genetic factors.…”
Section: Discussionmentioning
confidence: 96%
“…Although pediatric C-IMT does vary with height, weight, gender, blood pressure, and other cardiovascular biomarkers, childhood normal ranges have been published indicating a small increase over the first 20 years of life [16,17]. Corrected for other covariates, pediatric C-IMT is predictive of adult cardiovascular disease [18][19][20]. [4.2] This study establishes ultrasonographic evidence of carotid arterial wall thickening in this cohort of MPS patients compared to age, ethnicity, and gender-matched controls.…”
Section: [32] Carotid Intima-media Thickness and Echocardiographic Mmentioning
confidence: 99%